The origin of the forest-grassland mosaic of central Cameroon: What we learn from the isotopic geochemistry of soil organic matter. (October 2020) - Desjardins, Thierry; Turcq, Bruno; Lézine, Anne-Marie; Nguetnkam, Jean-Pierre; Mandeng-Yogo, Magloire; Cetin, Fethiye; Achoundong, Gaston
The end of the Holocene Humid Period was characterized by the massive collapse of forest ecosystems in central Africa. Was this large-scale environmental crisis dated between 3300 and 2500 years BP at the origin of the present-day wooded-grassland/forest mosaic of central Cameroon? Here we present carbon isotope data on soil organic matter collected from 29 sites from this area, including the Grassfield plateaus, with the aim of characterizing this environmental crisis and discussing the origin of the present-day landscape. 14 C data on total soil organic matter and charcoal fragments show that the organic matter in these soils originates from the Holocene. In our forest sites, the δ 13 C profiles do not show any marked alteration of the forest cover throughout the Holocene. Discrete traces of forest expansion or retreat are observed only punctually at the forest margins. In the wooded-grassland/forest mosaic zone, the environmental crisis was of reduced amplitude. In the present grassland and wooded grassland areas, there was no true forest during the lower to middle Holocene, but a markedly more tree-covered landscape. The timing of this crisis revealed by our 14 C measurements, although only indicative at this stage, suggests that it occurred earlier at higher altitudes than in the lowlands due to marked topographic relief favoring drainage along the slopes. These results fit a climatic rather than anthropogenic origin of the vegetation opening in this region.